2008
DOI: 10.1002/j.2168-9830.2008.tb00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Engagement: Contributions of Faculty to Student Engagement in Engineering

Abstract: The concept of student engagement, now prominent in the engineering education and higher education communities, has a long intellectual history. Yet only recently has attention focused on the role that faculty play as designers of educational environments to support student engagement. Drawing from examples and data from the Engineering Change study (which evaluated the impact of the new EC2000 accreditation standards on engineering programs and student learning), the Academic Pathways Study of the Center for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 33 publications
6
104
0
3
Order By: Relevance
“…There are two types of changes: professionals (how they analyze their professional future as this is approaching) and social (how they perceive the university and its integration within it). The latter has been proved to be vital as Chen et al (2008) and Lee et al (2006) studied, in the sense that it allows us to empower and strengthen aspiring and future engineering professionals to pursue, succeed and find fulfillment in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of changes: professionals (how they analyze their professional future as this is approaching) and social (how they perceive the university and its integration within it). The latter has been proved to be vital as Chen et al (2008) and Lee et al (2006) studied, in the sense that it allows us to empower and strengthen aspiring and future engineering professionals to pursue, succeed and find fulfillment in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…As well, it is comprised of the ways in which students approach these tasks with strong student engagement reflected in the use of independent and self regulated learning strategies [3]. Student engagement, at the course level, is characterized by "the student's concentration of attentional, cognitive and affective resources" [3, p. 339] towards the educational tasks to be completed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into student motivation has found that one of the key factors that motivates students in engineering is having instructors who care about them, 15,16 and this is borne out by her experiences in the program. She saw that students who felt that she connected with them on a personal level were more willing to work.…”
Section: Discussionmentioning
confidence: 99%